Dynamic land use/cover change modelling Geosimulation and multiagent-based modelling - Jokar Arsanjani, Jamal; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The thesis is an original and novel contribution to land use/land cover change analysis using methods of geosimulation and agent-based modeling. The author implements several traditional methodologies of land use change by means of remote sensing and GIS techniques. An Agent-Based Model was developed in order to simulate land use change in the Tehran metropolitan area, comparing the outcomes of each particular methodology. All methods are compared, and advantages and disadvantages discussed.
General Introduction -- Literature Review -- Study Area Description -- Data Preparation and Processing -- Implementation of Traditional Techniques -- Designing and Implementing Multi Agent Geosimulation -- Analysis of Results -- Conclusions and Recommendations.
Keywords: Geography; Remote sensing; Geographical information systems; Regional planning; Geography; Remote Sensing/Photogrammetry.; Landscape/Regional and Urban Planning; Geographical Information Systems/Cartography.